Knowledge Spillovers, Competition, and R&D Incentive Contracts - Nicola Lacetera; Lorenzo Zirulia (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2008)
This paper models the optimal provision of incentives to corporate scientists, within an environment where effort is multidimensional, firms compete on the product market, knowledge spills over across companies, and scientists have both monetary and non-monetary motivations. The simultaneous consideration of these aspects generates a number of novel results. First, knowledge spillovers lead firms to soften incentives in order not to benffit competitors, but only when product market competition is high. By contrast, greater knowledge spillovers positively affect the provision of incentives when competition is low. Second, the relationship between the intensity of competition and the power of incentives is U-shaped, and the region where the relationship is positive is smaller the higher the knowledge spillovers. Finally, both the incentives for applied and basic research increase with non-pecuniary benefits scientists obtain from basic research, while a trade-off between monetary pay and non-monetary rewards may occur at the level of the fixed salary. These results provide a novel interpretation of some observed R&D organizational choices by companies, offer insights for the management of scientific and other creative workers, and have implications for public policy.
Keywords: 330